Characterisation of protein unfolding by NMR diffusion measurements - Jones, J; Wilkins, D; Smith, L; Dobson, C (1997)
The characterisation of non-native states of proteins is a key problem in studies of protein folding. Complete characterisation of these states requires a description of both local and global properties, including molecular dimensions. Here we present results from pulsed field gradient experiments designed to compare the effective hydrodynamic radii of a protein in native and non-native states. Measurements performed on lysozyme indicate that the effective hydrodynamic radius increases by 38±1% on unfolding in urea, a result completely consistent with a recent study by small-angle X-ray scattering.